2003
DOI: 10.2308/aud.2003.22.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pressure from Potential Client Business Opportunities on the Judgments of Auditors across Professional Ranks

Abstract: This study examines the impact of the pressure to obtain potential client business opportunities on auditor judgments. Thirty-two lower rank auditors (staff and seniors) and 39 higher rank auditors (managers and partners) were either provided or not provided with information on additional client business opportunities when assessing a client's potential inventory obsolescence risk. Lower rank auditors judged the obsolescence risk to be lower when provided with information on additional business opportunities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
6
28
2
Order By: Relevance
“…This finding does not support the reasoning that higher-ranking auditors are more likely to withstand client retention incentives because they are more aware of the presence of counteracting incentives, such as litigation or reputation risks (e.g., Moreno and Bhattacharjee, 2003). Instead, our finding is in line with prior studies showing that auditors of higher rank are sensitive to client retention incentives, because their performance evaluation and compensation often rely strongly on the fee they generate (e.g., Haynes et al, 1998).…”
Section: Effects Of Client Retention Incentives and Client Typecontrasting
confidence: 52%
See 1 more Smart Citation
“…This finding does not support the reasoning that higher-ranking auditors are more likely to withstand client retention incentives because they are more aware of the presence of counteracting incentives, such as litigation or reputation risks (e.g., Moreno and Bhattacharjee, 2003). Instead, our finding is in line with prior studies showing that auditors of higher rank are sensitive to client retention incentives, because their performance evaluation and compensation often rely strongly on the fee they generate (e.g., Haynes et al, 1998).…”
Section: Effects Of Client Retention Incentives and Client Typecontrasting
confidence: 52%
“…For example, auditors are more willing to accept the accounting method proposed by the management when the risk of losing the client is high (e.g., Blay, 2005), when the client is important (e.g., Chang and Hwang, 2003), when the auditor's compensation scheme rewards client retention (e.g., Trompeter, 1994), or when the client represents future business opportunities (e.g., Moreno and Bhattacharjee, 2003). The potential negative effects of client retention incentives on auditors' independence are especially likely to occur when the auditor is highly committed to retaining the client (Kadous et al, 2003).…”
Section: Client Retention Incentives and Client Typementioning
confidence: 99%
“…However, empirical investigations examining demographic factors (such as gender, age, type and years of education, and individual's organizational rank) and ethical/unethical behavior have provided mixed results (Lund, 2000). A number of studies (e.g., Ponemon 1990Ponemon , 1992Shaub, 1994;Sweeney, 1995) found that moral reasoning measured by DIT decreased for CPAs with a higher rank in their firm, while other studies (e.g., Moreno and Bhattacharjee, 2003) using actual judgments such as potential obsolescence risk found higher ranked auditors to be more ethical (i.e., less susceptible to client pressure). Similarly, the results for the impact of gender have also been mixed with some studies (e.g., Shaub, 1994;Sweeney, 1995) finding that female CPAs have higher DIT scores than males while other studies (e.g., Ponemon, 1992;Ponemon and Gabhart, 1993) found no significant gender differences.…”
Section: Additional Analysesmentioning
confidence: 97%
“…Moreno and Bhattacharjee (2003) investigated the effects of auditor rank (staff/ senior vs. manager/partner) and the existence of other business opportunities related to the client (a potential consulting opportunity). Their primary dependent variable was the perceived risk that inventory is misstated given information indicating that some inventory potentially is obsolete.…”
Section: The Interaction Of Time Budget Pressure and Experiencementioning
confidence: 99%
“…2 The increased time pressure resulting from these new regulations may undermine the performance of auditors, especially less experienced auditors. Prior research has documented less experienced auditors' increased vulnerability to various pressure effects (e.g., Moreno & Bhattacharjee, 2003;Umar & Anandarajan, 2004) and negative effects of time pressures on audit performance (e.g., Malone & Roberts, 1996;Otley & Piece, 1996). With the current climate of diminishing confidence in the accounting profession due to corporate collapses and the related audit failures (Lin, Frazer, & Hatherly, 2003), research on how auditors with varying experience manage the efficiency-effectiveness tradeoff given time pressure seems especially important.…”
Section: Introductionmentioning
confidence: 99%